현월(玄月) 문학 속의 재일 제주인 - 황봉모(Hwang Bongmo) (외국문학연구, 2011)
현월은 1965년 오사카 大阪에서 태어난 재일한국인 2세로, 2000년「그늘의 집」이 아쿠타가와 상을 수상하면서 본격적으로 일본문단에 등단한 작가이다. 현월의 주요한 작품으로서는「무대배우의 고독」「나쁜 소문」「그늘의 집」「말 많은 개」「이물」「권족」등이 있는데, 그는 현재 일본문단에서 가장 활발하게 활동하고 있는 재일한국인작가 중 한명이라고 할 수 있다. 현월은 재일한국인이지만 재일한국인의 특수한 상황을 묘사하는 것보다 인간의 보편적인 면을 그리고 있는 작가라고 말하여진다. 그렇기에 이소가이 磯貝는 현월문학의 위상을 ‘탈구축과 구축의 더블 스탠딩’이라고 정의한다. 본고에서는 현월의 주요한 작품을 중심으로 하여, 그의 문학에 있는 재일 제주인에 대하여 고찰한 것이다. 재일 제주인은 일본에서 자신들만의 사회를 구축한다. 그들은 제주도의 문화, 풍속 등을 그대로 일본에 들여와 생활한다. 제주도의 시장, 제사, 한국 절, 그리고 자신들의 순수한 혈통을 잇기 위해서 제주도에서 며느리를 데리고 온다. 재일사회는 제주도의 축소판이었다. 즉 현월문학에 있는 한국은 제주도이고, 한국인은 제주도에서 온 사람들이다. 그리고 현월문학에 있는 제주도는 그리운 어머니의 모습과 연결된다. 이러한 제주도의 모습은 그에게 어머니와 같은 존재이기도 했다. 현월은 재일한국인에게 희망을 가지고 있다.「이물」에 나오는 ‘새로운 1세’들이 그들이다. 이 작품에서는 ‘새로운 1세’가 와서 마을 사람들과 함께 살아간다. 재일 2, 3세와 ‘새로운 1세’는 동세대여도 접점은 거의 없다. 그들에게 같은 피가 흐르고 있다고 해도 문화와 언어가 다르기 때문이다. 그러나 그들은 서로 사이좋게 지낸다. 현월은 이러한 ‘새로운 1세’들에게 희망을 발견한다. ‘새로운 1세’들에게 의해 마을에는 신진대사가 돌고 활성화된다고 보는 것이다. 현월이 보고 있듯이 이제부터 마을의 원래 주민들과 ‘새로운 1세’는 서로 도우면서 사이좋게 살아갈 것이다. Hyonyeol is a second generation Korean-Japanese who was born in Osaka in 1965, and was first recognized as a writer when his book of 2000 [The Shade House] received the akutagawa prize. He is one of the most well-known Korean writers who live in Japan, and his main novels include [Solitude of a Stage actor], [A Bad Rumor], [A Garrulous Dog], [A Foreign Body], [Kenzoku] and so on. He is known as a writer that portrays the universal aspects of humans rather than the special circumstances of Koreans living in Japan, though he himself is one. Thus, Isogai defines the phase of Hyonyeol’s literature as a double standing of deconstruction and construction. This article considers the Jeju residents in Japan that are shown in his literature, centering around his main work. The Jeju residents in Japan build their own society. They bring the culture and customs of Jeju-do into Japan and live by them. They also bring in the market system, a priest and a Buddhist temple from Jeju-do, and even a daughter-in-law from their main land in order to preserve the pure bloodline. Their society is a tabloid edition of Jeju-do. In other words, Korea in Hyonyeol’s literature is Jeju-do, and the people in there are Jeju residents. Also, Jeju-do in Hyonyeol’s literature is connected with the beloved mother. This sort of feature of Jeju-do was like a mother to the writer. Hyonyeol has hope for the Korean residents in Japan. The “new first-generation” that appears in [A Foreign Body] is those Koreans. In this novel, the “new first-generation” comes to Japan and lives among the villagers. Although the second and third generation and the “new first-generation” are of the same generation, they have no point of contact. This is due to the fact that their cultures and languages are different though the same blood flows within them. However, they get along just well. Hyunyeol finds hope in this kind of “new first-generation.” He thinks that the village metabolizes and revitalizes through this “new first-generation.” As Hyonyeol’ sees it, the original villagers and the “new first-generation” will help each other out and get along very well. KCI Citation Count: 2